2012
DOI: 10.1186/1471-2458-12-570
|View full text |Cite
|
Sign up to set email alerts
|

Does school-based physical activity decrease overweight and obesity in children aged 6–9 years? A two-year non-randomized longitudinal intervention study in the Czech Republic

Abstract: BackgroundGlobally, efforts aimed at the prevention of childhood obesity have led to the implementation of a range of school-based interventions. This study assessed whether augmenting physical activity (PA) within the school setting resulted in increased daily PA and decreased overweight/obesity levels in 6-9-year-old children.MethodsAcross the first to third primary school years, PA of 84 girls and 92 boys was objectively monitored five times (each for seven successive days) using Yamax pedometer (step count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
84
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 55 publications
3
84
0
10
Order By: Relevance
“…They have very low PA and increased their spontaneous PA in response to a strength-training intervention by 57%. 8 In prepubertal children, less specific types of strength-training interventions are also able to increase PA. Sigmund et al showed that 45 minutes more PE including highintensity activities such as jumps, hops, and sprints also increases leisure time PA. 23 The mechanism by which strength training induces spontaneous PA remains unclear. There may be an endocrine signaling coming from the musculoskeletal system, which is responsible for a positive feedback between physical strength and PA.…”
mentioning
confidence: 99%
“…They have very low PA and increased their spontaneous PA in response to a strength-training intervention by 57%. 8 In prepubertal children, less specific types of strength-training interventions are also able to increase PA. Sigmund et al showed that 45 minutes more PE including highintensity activities such as jumps, hops, and sprints also increases leisure time PA. 23 The mechanism by which strength training induces spontaneous PA remains unclear. There may be an endocrine signaling coming from the musculoskeletal system, which is responsible for a positive feedback between physical strength and PA.…”
mentioning
confidence: 99%
“…Because 12,000 steps/day correspond to approximately 60 min/day MVPA (Colley, Janssen, & Tremblay, 2012), it may be stated that 84% of the total sample met a recommendation for at least 60 min/day of MVPA. Th e recommended 90 min/day of MVPA (Sigmund, El Ansari, & Sigmundová, 2012) based on the number of steps/day, were performed by approximately 56% of children from the present study. Based on the results of the cpm of the accelerometer and their distribution by the CoP from Freedson et al (2005), we can say that 100% of our sample met the recommended 90 min/day of MVPA (Sigmund et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…According to Rosenkranz et al [50], teachers play a key role in motivating children to participate in physical education classes and physical activity. Sigmund et al [51] conducted a study of a school-based intervention that lasted 2 years and found that increased physical activity in schools had a positive impact on physical activity during leisure time and on weekends in the intervention group. In addition, family characteristics, such as parents' weight status, physical activity, and education, have a significant relationship with the weight status and lifestyle-related behaviors of the children [11,41,52,53].…”
Section: Discussionmentioning
confidence: 99%